Time perception of attractive male faces and voices: The role of women’s menstrual cycle - Nuno Fernandes; Sandra Soares; Mavilde Arantes; Joana Arantes (PLoS ONE, 2025)
Accurate time measurement is essential for organisms to synchronize their internal biological cycles with the external environment, crucial for reproductive success and survival. This study examines fluctuations in time perception across different phases of the menstrual cycle in response to visual and vocal attractiveness, building on previous research showing that women estimate longer viewing times for attractive male photos compared to unattractive ones. Forty-eight females participated in the experiment during both the menstruation and ovulation phases of their menstrual cycles, completing visual and auditory oddball tasks. Participants viewed a series of five stimuli and reproduced the duration of the last stimulus by pressing a mouse button. The final stimulus could be identical to the previous four (control trials), an attractive or unattractive male photo (visual attractiveness block), a masculinized or feminized male face (visual sexually dimorphic block), or a masculinized or feminized male voice (auditory sexually dimorphic block). Results indicated that duration estimates for masculinized male voices were significantly longer compared to feminized voices, while no differences were found for the menstruation phase. However, no differences were observed between the phases of the menstrual cycle in the visual conditions. Nevertheless, we replicate the temporal dilation effect associated with viewing attractive stimuli, suggesting an acceleration of the internal clock related to attractiveness perception. Our findings align with the literature on this phenomenon and provide initial evidence for an adaptive time perception mechanism influenced by the menstrual cycle, contributing to the understanding of the complex interactions between biological cycles and perceptual processes.